Development of an automatic portable chicken griller by using Arduino Uno microcontroller / Muhammad Uthman Shah Buddin, Muhammad Sarkhawi Ramli and Muhammad Syahmi Mohd Anuar - Shah Buddin, Muhammad Uthman; Ramli, Muhammad Sarkhawi; Mohd Anuar, Muhammad Syahmi (2015)
This project aims to demonstrate the use of microcontroller in developing an automatic chicken griller. The use of thermistor as a sensor for the microcontroller help to indicate either the chicken is cooked or not. Results show that temperature between 60 C to 70 C is chosen to be the suitable temperature for the chicken to be cooked. The output that indicates whether the chicken is cooked is controlled by the level of colored Light Emitting Diode (LED). Six red LEDs indicate the temperature level is low, while 3 green LEDs show the temperature level is at cooked level.